Uso clínico dos códigos CID: um estudo exploratório em larga escala - Nunes, Davidson Alves (2021)
The International Classification of Diseases (ICD) is a world reference in identifying diseases and health problems. The code is widely used for statistical studies, as well as for management, control, auditing and other purposes in healthcare. This exploratory study aims to provide an overview of the use of ICD-10 codes by physicians during patient care, evaluating most prevalent codes and investigating possible categorizations. We have collected and extracted more than 2.5 million electronic health records from 40 different hospitals in 256 clinics across Brazil. We identify the codes that most impact healthcare services and related medical specialties. Statistically, we draw two distinct distributions: scaled and linear. We look at relevant semantic groupings that can help code selection selection. In conclusion, we have identified the most prevalent problems in the service, the possible processes for filling in the codes, and propose changes in work activities and in the tool’s modeling.